1995
DOI: 10.1093/protein/8.10.1049
|View full text |Cite
|
Sign up to set email alerts
|

Deletion analysis of the starch-binding domain of Aspergillus glucoamylase

Abstract: INFORMATION TO USERSThis manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 107 publications
1
16
0
Order By: Relevance
“…With regard to the linker region connecting the other constitutive domains (especially the catalytic one) and an SBD, its length varies from a few to several tens of residues [15,17]. Although the SBD may behave as an independent structure‐functional module [18,21–23,39–41] with its own evolutionary history (this study), there should be a strong co‐operation between the SBD and the other constitutive domains (especially the catalytic one) via the linker region, as documented by studies with the glucoamylase from A. niger . It has been, for instance, revealed [42] that the C‐terminal part of the linker region has a destabilising effect on the catalytic domain, i.e.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…With regard to the linker region connecting the other constitutive domains (especially the catalytic one) and an SBD, its length varies from a few to several tens of residues [15,17]. Although the SBD may behave as an independent structure‐functional module [18,21–23,39–41] with its own evolutionary history (this study), there should be a strong co‐operation between the SBD and the other constitutive domains (especially the catalytic one) via the linker region, as documented by studies with the glucoamylase from A. niger . It has been, for instance, revealed [42] that the C‐terminal part of the linker region has a destabilising effect on the catalytic domain, i.e.…”
Section: Resultsmentioning
confidence: 86%
“…The SBD motif, consisting of several β‐strand segments forming an open‐sided, distorted β‐barrel structure [17,18], is responsible for the ability of an amylase to bind and digest the native raw, granular starch [19,20]. In α‐amylases the SBD may govern the enzyme thermostability [21], however, this motif seems to have nothing to do with thermostability in glucoamylases [22]. It has been demonstrated [23] that the SBD independently retains its function even if fused to a protein other than amylase.…”
Section: Introductionmentioning
confidence: 99%
“…Trp 563 in A. niger glucoamylase) is essential for digestion of raw starch, whereas the sequence around Trp 589 (Trp 590 ) contributes to the adsorption to raw starch [49]. Chen et al [50] studied mutant glucoamylase from A. awamori containing extensive deletions at the C-terminus of or within the SBD. They concluded that any deletion mutations in SBD result in diminution or loss of raw starch binding and digesting ability of the glucoamylase [50].…”
Section: The Binding Sites In Cbm20mentioning
confidence: 99%
“…Chen et al [50] studied mutant glucoamylase from A. awamori containing extensive deletions at the C-terminus of or within the SBD. They concluded that any deletion mutations in SBD result in diminution or loss of raw starch binding and digesting ability of the glucoamylase [50]. Using a similar approach with the α-amylase from Bacillus sp.…”
Section: The Binding Sites In Cbm20mentioning
confidence: 99%
“…The four conserved domains found in the CGTase of P. graminis translated sequence consisted of an alpha amylase catalytic (alpha-amyl, CDD:79479) domain and a C-terminus (Aamy_C, CDD:47909) domain, followed by a CGTase C-terminus domain (CGTase_C_t, CDD:30336) and a carbohydrate-binding Module-20 domain (CBM_ 20,CDD:79679). This last domain (conserved region of 90-130 amino acid residues) is shared by several amylolytic enzymes, acting on polysaccharides more rapidly than on oligosaccharides (Chen et al 1995).…”
Section: Resultsmentioning
confidence: 99%